Resiliência, perfil tipológico, e correlação com o comportamento auditivo em adultos - Faria, Sonia Aparecida [UNIFESP] (2019)
Objective: To identify the correlation between the pillars of resilience, the psychological types, and the auditory behavior of the adolescent and adult patients of the neuroaudiology clinic of the Federal University of São Paulo. Methods: We selected 89 individuals of both genders, between 16 and 60 years. The volunteers were submitted to tools of resilience scales, typology questionnaire, auditory behavior evaluation questionnaire and auditory processing evaluation battery. Results: Regarding gender, 65.2% were female and 34.8% were male. Of the 16 typologies, 12 were identified in the sample, 16.9% were Extroversion, Sensation and Feeling and 15.7% of the typology Introversion, Feeling and Sensation, both with greater expressiveness. The two typologies show the perceptual sensation function and the evaluative feeling function with a greater participation in the sample. As for the neurophysiological mechanisms of auditory processing, 24.7% impairment of in selective attention, 20.2% of temporal processing and 20.2% impairment of both selective attention and temporal processing. Statistical significance was identified between the resilience pillar of sociability and the 12 typologies of the sample, as well between the pillars of self-efficacy, good mood and positive orientation for the future and the neurophysiological mechanisms of hearing, selective attention and temporal processing. Conclusions: There was a positive correlation between the profiles of the psychological types, the pillars of resilience and the auditory behavior of the adolescent and adult patients of the neuroaudiology clinic.